Finding fungal ecological strategies: Is recycling an option?. (August 2020) - Zanne, Amy E.; Powell, Jeff R.; Flores-Moreno, Habacuc; Kiers, E. Toby; van 't Padje, Anouk; Cornwell, William K.
Abstract: High-throughput sequencing (e.g., amplicon and shotgun) has provided new insight into the diversity and distribution of fungi around the globe, but developing a framework to understand this diversity has proved challenging. Here we review key ecological strategy theories developed for macro-organisms and discuss ways that they can be applied to fungi. We suggest that while certain elements may be applied, an easy translation does not exist. Particular aspects of fungal ecology, such as body size and growth architecture, which are critical to many existing strategy schemes, as well as guild shifting, need special consideration in fungi. Moreover, data on shifts in traits across environments, important to the development of strategy schemes for macro-organisms, also does not yet exist for fungi. We end by suggesting a way forward to add data. Additional data can open the door to the development of fungi-specific strategy schemes and an associated understanding of the trait and ecological strategy dimensions employed by the world's fungi.